2009
DOI: 10.1371/journal.pone.0005626
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Short-Duration Sputum Pretreatment Procedures for Optimizing Smear Microscopy for Tuberculosis

Abstract: BackgroundDirect sputum smear microscopy for tuberculosis (TB) lacks sensitivity for the detection of acid fast bacilli. Sputum pretreatment procedures may enhance sensitivity. We did a pilot study to compare the diagnostic accuracy and incremental yield of two short-duration (<1 hour) sputum pretreatment procedures to optimize direct smears among patients with suspected TB at a referral hospital in India.Methodology/FindingsBlinded laboratory comparison of bleach and universal sediment processing (USP) pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 20 publications
4
13
0
Order By: Relevance
“…However, digestion and concentration of debris may also increase the number of false-positive results (7). Consistent with these observations, we found that bleach centrifugation microscopy was more sensitive than direct microscopy.…”
Section: Vol 48 2010 Bleach Microscopy For Tb Diagnosis 2437supporting
confidence: 89%
See 1 more Smart Citation
“…However, digestion and concentration of debris may also increase the number of false-positive results (7). Consistent with these observations, we found that bleach centrifugation microscopy was more sensitive than direct microscopy.…”
Section: Vol 48 2010 Bleach Microscopy For Tb Diagnosis 2437supporting
confidence: 89%
“…The pooled sensitivity was higher for bleach centrifugation (65%; 95% CI, 59 to 71%) than for direct (56%; 95% CI, 49 to 63%) microscopy. The results were similar when the two studies that used fluorescence staining (study b of Eyangoh et al [9] and the study of Daley et al [7]) were excluded from the analysis (data not shown). When sensitivity differences were pooled across studies, bleach centrifugation microscopy was 6% (95% CI, 3 to 10%; P ϭ 0.001) more sensitive than direct microscopy.…”
Section: Resultsmentioning
confidence: 61%
“…In order to control TB in Iran, attention should be paid to the quantity and quality of sputum smear. Sputum pretreatment procedures to optimize smear microscopy should be done in Iran (23). Prospective studies in Iran on a larger number of patients, considering the clinical diseases, quantity and quality of sputum, culture sputum, PCR, and viability stain microscopy with fluorescein diacetate are suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Ziehl Neelsen's (ZN) staining of sputum smear is the most widely used diagnostic technique for M. tuberculosis in developing countries, but it has limitation of the presence of minimum 1000 bacili/ mL of sputum sample [16]. The culture isolation technique is the gold standard method for tuberculosis diagnosis is, but require longer time duration for growth of M.tuberculosis isolates [17].…”
Section: Discussionmentioning
confidence: 99%